1979
DOI: 10.1007/bf00426942
|View full text |Cite
|
Sign up to set email alerts
|

Capillary supply and mitochondrial content of different skeletal muscle fiber types in untrained and endurance-trained men. A histochemical and ultrastructural study

Abstract: The number of capillaries per fiber, per mm2, around each fiber type and relative to fiber area was determined in six untrained subjects (UT) and six elite cross-country skiers (ET). Average values for maximal oxygen uptake were 49.8 ml . kg-1 . min-1 (UT) and 77.9 ml . kg-1 . min-1 (ET). Type I fibers constituted 39.2% (UT) and 68.6% (ET), type II A fibers 39.6% (UT) and 19.2% (ET), while 12.8% (UT) and 6.6% (ET) of the fibers were type II B. The mean fiber area for the type II A fibers was significantly grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
77
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 24 publications
7
77
0
2
Order By: Relevance
“…The methods used have been published elsewhere (Brodal et al 1977;Gr0nner0d, Dahl & Vaage, 1977;Ingjer, 1977;Ingjer, 1978a) and these studies shoud be consulted for particulars and discussion of their validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used have been published elsewhere (Brodal et al 1977;Gr0nner0d, Dahl & Vaage, 1977;Ingjer, 1977;Ingjer, 1978a) and these studies shoud be consulted for particulars and discussion of their validity.…”
Section: Methodsmentioning
confidence: 99%
“…Edstrom & Ekblom, 1972;Hoppeler, Luthi, Claassen, Weibel & Howard, 1973;Howald, 1975;Costill, Daniels, Evans, Fink, Krahenbuhl & Saltin, 1976;Brodal, Ingjer & Hermansen, 1977;Ingjer, 1978a). Although these studies indicate that training leads to an increase in the factors mentioned, it is impossible to decide with certainty whether the observed differences depend on the effect of training or on genetic differences.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is the most potent stimulator of angiogenesis in skeletal muscles, and few weeks of exercise training lead to measureable increases in muscle capillarization. Untrained subjects may enjoy 10-30 % increase in capillarization after 6-8 weeks of exercise training, whereas elite aerobic athletes with years of progressive exercise training express a capillary-to-muscle fiber ratio of more than 200 % of that of untrained individuals (Ingjer 1979). During exercise, vascular endothelial growth factor (VEGF) is secreted from the muscle fibres to the muscle interstitium.…”
mentioning
confidence: 99%
“…Skeletal muscle hypertrophy is associated with blood vessel recruitment, such that capillary density is either maintained or increased during muscle growth (1)(2)(3)(4). A number of studies have shown that the serine-threonine protein kinase Akt1 plays a key role in regulation of cellular hypertrophy and organ size (5).…”
mentioning
confidence: 99%
“…The expression of constitutively active Akt1 in skeletal muscle stimulates muscle hypertrophy both in vitro and in vivo (6 -9). Adenovirus-mediated transduction of constitutively active Akt1 also promotes the induction of the vascular endothelial growth factor (VEGF), 3 and this is accompanied by an increase in limb perfusion and capillary density in muscles where Akt1 is overexpressed (6). Constitutive activation of Akt1 in the heart also promotes myocardial angiogenesis, which is partly mediated by the induction of VEGF (10,11).…”
mentioning
confidence: 99%